Paradoks PKPU sebagai Instrumen Perdamaian yang Berujung Kepailitan pada Kasus PT Alamsari Lestari - Silalahi, Udin; Yap, Abigail Angeline; Maharani, Aurelia Gisa; Putri, Rafirstka Madyah; Nevada, Valonia (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
This study examines the legal analysis of the fulfillment of formal and material requirements in the voluntary petition for Suspension of Debt Payment Obligations filed by PT Alamsari Lestari. The research is based on the decision of the Commercial Court at the Central Jakarta District Court Number 137/Pdt.Sus-PKPU/2023/PN Niaga Jkt.Pst and the provisions of Law Number 37 of 2004 concerning Bankruptcy and the Suspension of Debt Payment Obligations. The findings indicate that PT Alamsari Lestari has fulfilled both formal and material requirements for submitting a voluntary petition. Formally, the company obtained approval from the General Meeting of Shareholders (RUPS) and submitted the petition in accordance with procedural rules. Materially, PT Alamsari Lestari was proven to have debts to more than one creditor, with obligations that had fallen due and could be claimed. The court’s consideration in granting the petition serves as a preventive measure to avoid bankruptcy and allows the company to restructure its debts through a legally supervised peace plan. This case reflects how the Suspension of Debt Payment Obligations functions as an instrument to balance the interests of debtors and creditors under Indonesian bankruptcy law.